2011
DOI: 10.4236/aim.2011.11002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Various Crude Extracts of <i>Zingiber officinale</i> Rhizome for Potential Antibacterial Activity: A Study <i>in Vitro</i>

Abstract: In vitro antibacterial activity of crude aqueous and organic extracts of rhizome of Zingiber officinale Roscoe (ginger) was studied against both Gram-negative (Escherichia coli and Salmonella typhi) and Gram-positive (Bacillus cereus, Bacillus subtilis, Staphylococcus aureus and Streptococcus pyogenes) bacterial strains. The present study reveals that the pattern of inhibition varied with the solvent used for extraction and the organism tested. Plant extracts prepared in organic solvents provided more consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 11 publications
(15 reference statements)
3
17
0
1
Order By: Relevance
“…These compounds were associated with the antimicrobial efficiency of extracts in disk diffusion assay against gram-positive and gram-negative bacteria. The extracts were more effective against gram-positive than gram-negative bacteria as reported by Kaushik and Goyal (2011). The higher resistance of gram-negative bacteria could be due to the complexity of the cell wall (ROMANIUK; CEGELSKI, 2015;SILHAVY et al, 2010;TEJADA et al, 2013).…”
Section: Antimicrobial Activity: Extracts Of Zingiber Officinale Roscoementioning
confidence: 78%
See 3 more Smart Citations
“…These compounds were associated with the antimicrobial efficiency of extracts in disk diffusion assay against gram-positive and gram-negative bacteria. The extracts were more effective against gram-positive than gram-negative bacteria as reported by Kaushik and Goyal (2011). The higher resistance of gram-negative bacteria could be due to the complexity of the cell wall (ROMANIUK; CEGELSKI, 2015;SILHAVY et al, 2010;TEJADA et al, 2013).…”
Section: Antimicrobial Activity: Extracts Of Zingiber Officinale Roscoementioning
confidence: 78%
“…Zingiber officinale, popularly known as ginger, is widely cultivated for the use of spices, condiments, and medicinal applications, in which the most utilized part of the plant is the rhizome (KAUSHIK; GOYAL, 2011;RAJSEKHAR et al, 2012;SUHAD et al, 2012). The rhizome contains approximately 1-4% of the volatile oils that are responsible for the taste, aroma, and medicinal potential unique to ginger.…”
Section: Zingiberaceae: Antimicrobial Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the ginger ethanol extracts showed better activity than isopropyl-hexane (7:3) extracts. Another study showed that methanol and ethanol ginger extracts exhibit a broad antibacterial spectrum activity while control experiments with only the solvents showed no inhibition of any bacteria, indicating that ginger itself and not the solvent inhibited the growth of the bacteria 17 . The antibacterial activity is most likely due to the phytoconstituents present in ginger.…”
Section: Discussionmentioning
confidence: 99%